Body fat evaluation in Colombian Paso horses: body condition score and morphometric and ultrasound measurements (2020)
ABSTRACT: The body condition score (BCS) is insufficient in determining the amount of body fat in horses, thus defining obesity. Measurement of the subcutaneous fat thickness (SFT) by ultrasonography should be considered as an appropriate method in the definition of fat distribution at different body locations in horses. Therefore, this study aimed to 1) characterize the SFT in three different anatomical locations (i.e. neck, lumbar region, and gluteal region); 2) evaluate the relationship between BCS and SFT; 3) determine the influence of gender, weight, age, and gait on BCS and SFT measurements, and 4) explore the agreement between the morphometric measurements [i.e. body mass index (BMI), girth circumference: height at withers ratio (GC: HW), neck circumference: height at withers ratio (NC: HW)], and BCS and SFT in a population of Colombian Paso Horses (CPHs). The Henneke’s body condition scoring was applied to 69 adult CPHs, selected using a convenience sampling. Additionally, BMI, GC: HW, and NC: HW were calculated. Body fat percentage (BF%) was calculated by ultrasound measurement of the SFT in the neck, lumbar region, and gluteal region. The BF% in the CPHs was 6.4 ± 1.1. The GC: HW, NC: HW, and BMI were not predictors of the BF% or BCS, and neither gender nor gait was decisive in the definition of fattening in the study animals, although age and weight were determining variables. According to our results, ultrasound is an adequate tool to calculate the BF% of the CPHs. However, it must be accompanied by Henneke’s BCS assessment.